Rituals and ritual theory in ancient Israel - Gruenwald, Ithamar (Brill reference library of Judaism, 2003)
This work covers the issues of rituals and their embedded ritual theory in the religion of ancient Israel. It states that rituals are an autonomous form of expression of the human mind. It argues that the ritual theory is not in any general theory of ritual but embedded in the ritual act itself.